2012
DOI: 10.1590/s1678-77572012000100004
|View full text |Cite
|
Sign up to set email alerts
|

Diametral tensile strength and film thickness of an experimental dental luting agent derived from castor oil

Abstract: The need to develop new dental luting agents in order to improve the success of treatments has greatly motivated research.ObjectiveThe aim of this study was to evaluate the diametral tensile strength (DTS) and film thickness (FT) of an experimental dental luting agent derived from castor oil (COP) with or without addition of different quantities of filler (calcium carbonate - CaCO3).Material and MethodsEighty specimens were manufactured (DTS N=40; FT N=40) and divided into 4 groups: Pure COP; COP 10%; COP 50% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 24 publications
0
11
0
1
Order By: Relevance
“…The calcium carbonate filler was used because previous studies have shown its ability to provide radiopacity to the COP and to supply bactericidal and fungicidal properties to the cement, properties that can be a key factor in the selection of a dental luting agent. The addition of 10% calcium carbonate showed good results regarding diametral tensile strength and film thickness 6 .…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…The calcium carbonate filler was used because previous studies have shown its ability to provide radiopacity to the COP and to supply bactericidal and fungicidal properties to the cement, properties that can be a key factor in the selection of a dental luting agent. The addition of 10% calcium carbonate showed good results regarding diametral tensile strength and film thickness 6 .…”
Section: Discussionmentioning
confidence: 96%
“…The COP was provided in a sachet containing polyol, prepolymer and calcium carbonate 6 . This polyurethane has the following highly reactive groups in the ricinoleic acid structure: a carbonyl group on the first carbon, a double bond (or unsaturation) on the ninth carbon and a hydroxyl group on the twelfth carbon.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Dodatkowo pozwala uniknąć trudności, które pojawiają się podczas przygotowywania próbek do badań wytrzymałości na zginanie. 20,21 Biorąc pod uwagę fakt, że wiele niepowodzeń klinicznych spowodowanych jest siłami rozciągania uznaje się, że średnicowa wytrzymałość na rozciąganie materiałów kompozytowych ma większą wartość kliniczną niż wytrzymałość na ściskanie. 22 W badaniach własnych wykazano, że wartości DTS dla badanych materiałów mieściły się w zakresie od 26 do 59 MPa.…”
Section: Dyskusjaunclassified